English Proficiency and Academic Success: A Study of Chinese Students in UK Higher Education - Michael Daller (Vocabulary studies in first and second language acquisition: The Interface Between Theory and Application, 2009)
The number of Chinese students undertaking international education has been increasing steadily over the past decade, and this upward trend is still ongoing (Goh, 2007; TEIU, 2008). Study failure is obviously a major concern for both international students themselves and universities in host countries. Previous attempts to relate the study success of overseas students to their English language proficiency have used scores from standardized tests such as the International English Language Test System (IELTS) or the Test of English as a Foreign Language (TOEFL). Whilst such tests are valid tools as entry tests (Rosenfeld et al., 2004; Taylor & Falvey, 2007), they do not seem to be good predictors of academic success on their own. We therefore tried to find other measures to complement the information provided by IELTS by using data from 23 overseas students from China in the present study. Apart from their IELTS scores, we used two measures of lexical diversity (‘D’ & Guiraud) and two measures of lexical sophistication (Lexical Frequency Profile & Guiraud Advanced) based on their written essays. In addition, we employed C-tests which focus on vocabulary but also measure other aspects of foreign language proficiency (Eckes & Grotjahn, 2006). The correlations we found clearly showed that the C-tests focused on lexical sophistication rather than diversity. The present study revealed the C-test to be a powerful tool in that it allowed us to predict over one-third of the variance of the modules failed by the students during their first year in UK higher education (HE). We conclude that lexical sophistication is most closely related to overseas students’ academic success.